Legal Liability of Bottled Drinking Water Companies for Circulating Reusable Gallons Beyond Their Lifespan - Nelvina Djaja; Audrianna Richella; Michelle Jesslyn; Jerry Shalmont (Jurnal Cakrawala Hukum, 2026)
This article analyses the legal liability of bottled drinking water (BDW) companies for circulating reusable gallon containers exceeding their technical lifespan, focusing on corporate-compliance failure and its consumer-protection implications. Normatively (das sollen), Law Number 8 of 1999 on Consumer Protection guarantees consumers’ rights to comfort, security and safety; empirically (das sein), findings by the Indonesian Consumers Community (KKI) in late 2025 show that 57 per cent of reusable gallons circulating in Jabodetabek have exceeded their reasonable lifespan, exposing consumers to polycarbonate degradation and potential Bisphenol-A (BPA) migration. Using a normative juridical method with statutory and conceptual approaches, this study finds such practices constitute both a corporate-compliance failure and a violation of consumers’ rights under Articles 4, 7 and 8 of Law Number 8/1999. The absence of an explicit, quantitative lifespan standard is identified as a normative gap perpetuating information asymmetry between business actors and consumers. Compared with the European Union’s stricter BPA trajectory and neighbouring ASEAN jurisdictions, whose BPA bans remain confined to infant feeding bottles, Indonesia’s migration limit lags both international and regional consensus. The study recommends strengthening corporate compliance and internal control, together with regulatory reform establishing explicit lifespan and refill-cycle limits for reusable gallon containers.